2009
DOI: 10.1074/jbc.m109.037036
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dimethylarginine Dimethylaminohydrolases in the Regulation of Endothelial Nitric Oxide Production

Abstract: Reduced NO is a hallmark of endothelial dysfunction, and among the mechanisms for impaired NO synthesis is the accumulation of the endogenous nitric-oxide synthase inhibitor asymmetric dimethylarginine (ADMA). Free ADMA is actively metabolized by the intracellular enzyme dimethylarginine dimethylaminohydrolase (DDAH), which catalyzes the conversion of ADMA to citrulline. Decreased DDAH expression/activity is evident in disease states associated with endothelial dysfunction and is believed to be the mechanism r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 45 publications
8
50
0
Order By: Relevance
“…Investigations of ADMA concentration by independent methods in patients with renal failure, have identified plasma ADMA concentration as a strong independent predictor of disease progression. Of particular interest was the finding that a 0.1 µmol/L increase in plasma ADMA was associated with a 20% increase in cardiovascular event rate [7,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigations of ADMA concentration by independent methods in patients with renal failure, have identified plasma ADMA concentration as a strong independent predictor of disease progression. Of particular interest was the finding that a 0.1 µmol/L increase in plasma ADMA was associated with a 20% increase in cardiovascular event rate [7,33].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have demonstrated that modulating DDAH activity can have a profound effect on endothelial NO production [7,36,37]. Two isoforms of DDAH have been identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41,42 Additionally, Pope et al concluded that DDAH-mediated endothelium function "is largely ADMA-dependent and latter ADMA-independent." 43 On the other hand, since ADMA is taken up by endothelium, ADMA could accumulate and metabolize by DDAH intracellularly. 44 Hcy is a metabolic byproduct forming during the methionine cycle.…”
Section: Discussionmentioning
confidence: 99%